2021
DOI: 10.1021/acs.jced.1c00098
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Speed of Sound for 3,3,3-Trifluoropropene (R-1243zf) in Gaseous Phase Measured with Cylindrical Resonator

Abstract: The speed of sound in 3,3,3-trifluoropropene (R-1243zf) in the gaseous phase has been measured using a fixed-path cylindrical resonator. The experiment was conducted along nine quasi-isochoric lines in the temperature range of (313 to 363) K and pressure range of (170 to 983) kPa. The speed of sound at 92 state points (p,T) was obtained from accurate measurements of resonant frequencies of seven acoustic modes. The overall relative expanded uncertainty at the confidence level of 0.95 in the speed of sound meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(63 reference statements)
2
10
0
Order By: Relevance
“…Sheng et al [7] reported the data set for isochoric specific heat. As same as the specific-heat data, the speed-of-sound data was reported by Chen et al [8]. Both data are newer than the existing EOS of Akasaka and Lemmon [6].…”
Section: Survey and Available Datasupporting
confidence: 64%
See 2 more Smart Citations
“…Sheng et al [7] reported the data set for isochoric specific heat. As same as the specific-heat data, the speed-of-sound data was reported by Chen et al [8]. Both data are newer than the existing EOS of Akasaka and Lemmon [6].…”
Section: Survey and Available Datasupporting
confidence: 64%
“…When the Akasaka and Lemmon equations [6] were developed, data for the isobaric-specific heat of an ideal gas were not yet available, so the data from analytical modeling based on the molecule's shape using the Joback-Reid method [17] was used. Now available data from the experimental results can be used, namely data from Chen et al [8]. The amount of data generated is very limited, but its role is essential to verify and improve the quality of the previous equation.…”
Section: Survey and Available Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The fixed-path acoustic resonance method, which was comprehensively introduced in the study by Moldover, was selected as the experimental method to measure the speed of sound. The method is currently one of the most accurate for measuring the gaseous speed of sound, and it has been used for determining the Boltzmann constant ( k B ) and redefining the thermodynamic temperature reference in SI. , Our previous studies demonstrated that this method is suitable for measuring the speed of sound in HFOs and their blends. , Briefly, an acoustic standing wave is formed in a fixed cylindrical or spherical cavity, and then the speed of sound is calculated using the measured resonance frequency and the calibrated cavity length according to the wave equation. For a cylindrical cavity, the speed of sound ( w ) is calculated according to eq . w = 2 π ( f N j normalΔ f j ) / true( l π L true) 2 + true( χ m n a true) 2 where f N is the measured resonant frequency, Δ f j is the shift in the measured resonant frequency from the ideal frequency owing to the nonidealities, l ,| m |, n = (0, 1, 2···) are characteristic numbers of the axial, angular, and radial vibrations, respectively, indicating the number of half-waves in each direction, L and a are the length and radius of the resonant cavity, respectively, and χ mn is the zeros of the first derivative of the cylindrical Bessel function.…”
Section: Methods and Instrumentsmentioning
confidence: 99%
“…Kano et al (2020) [141] provided 36 data for the vapour phase speed of sound of R1224yd(Z), with reduced temperatures between 0.71 and 0.82 and reduced pressures between 0.04 and 0.20: deviations from REFPROP are small in all these ranges, with AAD% = 0.01 and MAD% = 0.04. On the other hand, Chen et al (2021) [142] measured the vapour phase speed of sound of R1243zf (92 data) in the ranges T r = 0.83 to 0.96 and P r = 0.05 to 0.28. Deviations from REFPROP are systematically negative and higher for conditions further from the critical region (AAD% = 0.198, MAD% = 0.44).…”
Section: Speed Of Soundmentioning
confidence: 99%